1991
DOI: 10.1051/lait:1991647
|View full text |Cite
|
Sign up to set email alerts
|

Bitter flavour in dairy products. I. A review of the factors likely to influence its development, mainly in cheese manufacture

Abstract: Summary -Following a definition of bitte mess and a mention of the Iink between the bitterness of peptides and their content of hydrophobie amino acid residues, a detailed description is given of the numerous factors Iikely to influence the development of bitter off-flavour defect in dairy products with emphasis on cheese. Factors such as milk quality, pH, psychrotrophic bacteria, fat and minerai content, the cheese manufacturing process including the cooking temperature, salt concentration and manner of drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
10

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 50 publications
1
64
0
10
Order By: Relevance
“…Even the recent review on bitter flavor in dairy products (Lemieux and Simard, 1991;1992) ignored the discussion on this part. In this brief review efforts have been given to discuss the issue according to the scheme presented in Figure 4 (Schmidt, 1990) • • particularly emphasized on the role of proteases and peptidases of non starter microflora.…”
mentioning
confidence: 99%
“…Even the recent review on bitter flavor in dairy products (Lemieux and Simard, 1991;1992) ignored the discussion on this part. In this brief review efforts have been given to discuss the issue according to the scheme presented in Figure 4 (Schmidt, 1990) • • particularly emphasized on the role of proteases and peptidases of non starter microflora.…”
mentioning
confidence: 99%
“…During hydrolysis pepdides of varying sizes are formed but it is well known that some pepdides, especially those rich in hydrophobic amino acids taste bitter. Bitterness is influenced by the cheese making procedure and by factors such as strain of starter culture, rennet concentration, heat treatment of the milk, acidity or pH of cheese and salt concentration [41], [42].…”
Section: Resultsmentioning
confidence: 99%
“…Lemieux and Simard [41] and Urbach [43] observed that Val, Leu, Pro and Phe are major FAAs which forming bitterness. Kabelova et al [44] reported that individual amino acids, seven amino acids were more concentrated in all cheese samples, and came from three distinctive taste groups: bitter tasting amino acids (Leu, Lys, and Phe), bitter sweet amino acids (Pro and Val), and salty-umami amino acids (Glu and Asp).…”
Section: Resultsmentioning
confidence: 99%
“…Par ailleurs, un défaut d'amertume était souvent observé chez les fromages affinés (Tab. III), qui pourrait être dû à des quantités importantes de mono et diglycéri-des, à la présence de peptides hydrophobes issus de la protéolyse [24] et à un effet des sels tels que CaCl 2 et MgCl 2 [9].…”
Section: Discussionunclassified
“…Des quantités importantes de ces acides gras libres peuvent être préjudiciables à la flaveur du lait et des produits laitiers, en entraînant l'apparition de flaveurs rance, savon, ou piquante [3,32]. Par ailleurs, la libération de mono et diglycérides qui accompagne la lipolyse peut-être à l'origine d'un défaut d'amertume dans les fromages [24]. Toutefois, la flaveur caractéristique des produits laitiers caprins est due en grande partie à certains acides gras libres, notamment aux acides gras ramifiés 4-ethyl-C8 et 4-methyl-C8 [19,25] et une corrélation entre la lipolyse et la flaveur « chèvre » du lait a été montrée [5,19,22,25,31].…”
Section: Introductionunclassified